Intervensi Berbasis Digital Efektif Meningkatkan Kemampuan Matematika pada Siswa: Studi Metaanalisis - Cynthia Vivian Purwanto; Ananta Yudiarso (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2021)
Numeracy is one of the most necessary skills needed. However, not every student has sufficient numeracy, therefore it is needed an effective intervention to improve students’ mathematics skill. The widely use of technology in education has provided a breakthrough for conducting digital-based interventions in learning mathematics. This study goal is to review the literature which measures the effectiveness of digital-based intervention to improve mathematics skill. Meta-analysis done to eighteen journals published in the past decade with 1,721 participants of experiment group and 1,219 participants of control groups which are relevant to this study. Based on mean differences (M, SD, and n) analysis, it is found that the effect size was g = .492 (95% CI = [.287, .706]; p < .001; I2 (inconsistency) = 84.43%). This shows that the effect size obtained is similar to Benavides-Varela et al. (2020) study which found digital-based interventions are effective to improve dyscalculia students’ mathematics skill. There is also no evidence which shows level of education affects the use of digital intervention to improve students’ mathematics skill (p = .359). The effect size obtained while using level of education as moderator is g =.398 (95% CI = [-.483, .175]; p < .001; I2 (inconsistency) = 84.02%). Therefore, educators can use digital media as a tool to support students’ mathematics learning, both at the preschool to college level.